Determinants of Behavioural Intention to Use Islamic Financial Technology in Generation Z - Fahrunnisa, Anis; Puspawati, Dewita (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Islamic financial technology in Indonesia in the current era is increasingly being used, especially by Generation Z. Generation Z grows up and lives when financial technology is more advanced and developed. This study aims to determine the behavioral intention to use Islamic financial technology in generation Z. The method in this study is to use the UTAUT2 model and analyze it using Structural Equation Modeling (SEM) and Partial Least Square (PLS) in the SmartPLS 4.0 program. The sample in this study was generation Z in Surakarta who had never used Islamic bank services, totaling 115 respondents. The results in this study indicate that Effort Expectancy, Habit, and Hedonic Motivation have a significant effect on behavioral intentions to use Islamic Financial Technology, while Performance Expectancy, Social Influence, Facilitating Conditions, and Price Value have no significant effect on behavioral intentions to use Islamic Financial Technology.